Methylation associated pathway activity deregulation in lung adenocarcinoma - Nersisyan, L.; Löffler-Wirth, Henry; Gevorgyan, A.; Binder, Hans; Arakelyan, A. (European Respiratory Journal, 2014)
Methylation impairments are tightly associated with gene expression and molecular pathway deregulation in cancer development. However, other regulatory mechanisms exist, making it important to distinguish those from methylation driven changes. Here we specifically assessed molecular pathway states associated with gene methylation in lung adenocarcinoma.